DONATION MOVEMENT AS THE IMPLEMENTATION OF CITIZENSHIP EDUCATION IN THE DISRUPTION ERA - Rossa Handini; Reinhard Immanuel Setiawan; Evan Jonatan Satyagung; Oliviero Michael Putra Rasetya; Moses Glorino Rumambo Pandin (Academy of Education Journal, 2022)
In the development of the era of disruption, the role of students is required to have above average ability, to compete in the world of work. From these demands, allowing the emergence of apathy towards the social environment that does not follow the values of citizenship, then came the solution of the donation movement to stem the apathy of students in the era of civic education-based disruption. Therefore, researchers want to find out if the sense of humanity in this era of disruption is reduced? Is the donation movement the right solution to overcome the lack of humanity in the era of disruption? The research method used is a combination of quantitative and qualitative through E-surveys and interviews to 40 student respondents of Universitas Airlangga 2021, five out of 40 representing interviews. From the results of the research obtained that the donation movement is the right solution for students to foster a sense of humanity through civic education.